Lived experiences of nurse educators on teaching in a large class at a nursing college in Gauteng - Maria G. Ndawo (AOSIS, 2016)
Background: The gradual increase in the number of learners admitted into a nursing college in Gauteng resulted in an increase in class size without a proportional increase in the number of nurse educators. Objectives: To explore and describe the experiences of nurse educators teaching in large classes at a nursing college in Gauteng in order to present recommendations to facilitate teaching and learning. Method: A qualitative, exploratory, descriptive, and phenomenological research design which is contextual in nature was used. A total of 20 nurse educators were selected through purposive sampling, and in-depth phenomenological semi-structured individual interviews were conducted between January and February 2013. Data were analysed together with the field notes, using Tesch's open coding protocol of qualitative data analysis. Lincoln and Guba's four principles were used to ensure trustworthiness. Results: The themes that emerged from this study were that nurse educators experienced difficulty in recognising learners as individuals in a large class, using innovative pedagogical strategies, and managing a large class. These findings had a negative impact on meaningful teaching and learning as they interfered with an enabling learning environment. Recommendations: Nurse educators should be empowered with facilitative skills in order to effectively manage a large class and hence to achieve teaching and learning abilities. Conclusion: There is a need for nurse educators to finding alternative ways to overcome challenges associated with teaching in large classes and prepare learners to render individualised, caring and holistic nursing care to each unique patient in the healthcare setting. Keywords: Large class, Teaching, Learning; Hindrance